O neotribalismo e outras socializações pós-modernas - CASTRO, Fábio Fonseca de (Universidade Federal do Rio de Janeiro, 2022)
This article updates the debate on neo-tribalism, a phenomenon first identified with post-industrial societies and then understood as a common cultural process of contemporaneity, in light of the reflections on the dynamics of socializations and sociability production, developed by the Center for Cultural Contemporary Studies at the University of Birmingham (CCCS), in the first case, and G. Simmel’s philosophy in the second. We discuss the idea of neo-tribalism using major catego ries that are used to describe the phenomenon: spatiality / nomadism and temporality / presentism.